Perlindungan Hukum Bagi Penumpang Pesawat Udara Jika Terjadi Keterlambatan Jadwal Penerbangan Menurut Undang - Undang Nomor 1 Tahun 2009 Tentang Penerbangan - Ni Made Trisna Dewi (Fakultas Hukum, Universitas Warmadewa, 2021)
Air transportation services are currently experiencing very rapid development, this is indicated by the emergence of many various air transportation service providers in the Indonesian market. Many passenger rights are not properly cared for or fulfilled by the airline, especially if things happen that are not desired, one of which is the case of flight schedule delays. The formulations of the problems in this study are: 1) What is the legal protection for airplane passengers if there is a delay in flight schedules according to Law No.1 of 2009, 2) What are the efforts that aircraft passengers can make if they have been harmed due to flight schedule delays. This type of research is normative legal research. This study uses the Legislative Approach. The conclusion of this research is that the airline is responsible for delays in flight schedules that cause losses to passengers, here the airline applies the concept of presumption of liability. However, on the one hand, there is a condition where if the delay is due to weather and technical operational factors, the airline is not required to provide compensation to passengers in accordance with Article 146 of Law Number 1 of 2009. The process of compensation activities between consumers and airlines can be carried out when the consumers fly. a summons to the airline, but if it is ignored, the consumer can take court or outside the court route according to law number 8 of 1999 concerning consumer protection.